The Role of Heme and Reactive Oxygen Species in Proliferation and Survival of Trypanosoma cruzi - Marcia Cristina Paes; Daniela Cosentino-Gomes; Cíntia Fernandes de Souza; Natália Pereira de Almeida Nogueira; José Roberto Meyer-Fernandes (Journal of Parasitology Research)
Trypanosoma cruzi, the protozoan responsible for Chagas disease, has a complex life cycle comprehending two distinct hosts and a series of morphological and functional transformations. Hemoglobin degradation inside the insect vector releases high amounts of heme, and this molecule is known to exert a number of physiological functions. Moreover, the absence of its complete biosynthetic pathway in T. cruzi indicates heme as an essential molecule for this trypanosomatid survival. Within the hosts, T. cruzi has to cope with sudden environmental changes especially in the redox status and heme is able to increase the basal production of reactive oxygen species (ROS) which can be also produced as byproducts of the parasite aerobic metabolism. In this regard, ROS sensing is likely to be an important mechanism for the adaptation and interaction of these organisms with their hosts. In this paper we discuss the main features of heme and ROS susceptibility in T. cruzi biology.